Dual characterization of biological cells by optofluidic microscope and resistive pulse sensor. Issue 3 (2nd October 2014) - Guo, Jinhong; Chen, Liang; Huang, Xiwei; Li, Chang Ming; Ai, Ye; Kang, Yuejun; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> Label‐free detection technique has emerged as a powerful platform for biomedical applications since it can avoid laborious multi‐step sample preparation. In this paper, we demonstrate a dual analysis of biological cells using a single microfluidic system combining optofluidic microscopy and resistive pulse sensing. Both red blood cells (RBCs) and circulating tumor cells (CTCs) have been used to validate the concept of dual analysis and also to test the performance of the microfluidic device. The cell characterization by resistive pulse sensing is in good agreement with the analysis by optofluidic microscopy, further verified by the commercial Beckman‐Coulter® FC500 flow cytometry. The present system has attractive merits such as simple fabrication, easy integration, high portability, and low cost. This study has great potentials for the development of innovative on‐chip flow cytometry with concurrent imaging sensing and resistive sensing.